Analisis Sebaran Spasial Kontribusi Ekosistem Mangrove Sebagai Blue Carbon Dalam Implementasi FOLU Net Sink Di Pulau Lombok - Anis Syakiratur Rizki; Alfian Pujian Hadi; Nuzuly Ilmia Cerminand; Mai Rizali; Baiq Farista; Arben Virgota (Bioindikator: Jurnal Biologi dan Pendidikan Biologi, 2024)
Mangrove ecosystems have a strategic role as significant carbon absorbers (blue carbon) in supporting climate change mitigation. This study aims to analyze the spatial distribution of the contribution of mangrove ecosystems as blue carbon in the context of the implementation of FOLU (Forestry and Other Land Use) Net Sink on Lombok Island. The methodology used involves remote sensing data analysis, spatial mapping, and carbon stock calculations based on mangrove biogeophysical parameters. The results of the study indicate that the distribution of mangrove ecosystems on Lombok Island is uneven with the highest carbon potential found in areas with the highest mangrove ecosystem area, these results indicate that East Lombok Regency has the largest mangrove area spread across Gili Lawang Mangrove (429.18 ha) and Gili Sulat (683.30 ha), as well as several other locations such as Gili Petagan (79.34 ha), Seruni Mumbul (11.27 ha), and Teluk Jor (66.69 ha). The highest carbon storage potential estimate is in Gili Sulat with a total of 110,537 tons, and Gili Lawang reaching 69,428.4 tons. The large potential for carbon storage and absorption contributes to the value of ecosystem services with the largest estimate found in the Gili Sulat mangrove ecosystem (IDR 30.39 billion) and Gili Lawang (IDR 19.09 billion). The blue carbon potential estimate of the Lombok Island mangrove ecosystem can be influenced by factors such as area size, type of vegetation, and ecosystem conditions as the main determinants of carbon storage estimates (carbon sink), carbon dioxide absorption (CO2), and oxygen production (O2).